Compelling Stories and Storytelling: An Time-Honored Approach from Civilization’s Historical Roots: Practical Frameworks, Tips, and Examples for Entrepreneurs and New Ventures - York, John M. (Archives of Business Research, 2021)
Stories and storytelling date back to humankind’s earliest times. Stories have served as a primary avenue for sharing knowledge, history, culture, and information across civilizations. They present an essential mechanism for promoting new ideas and persuading points of view. Successful TED talks highlight how critical stories are in opening a presentation, engaging the audience, and taking participants on the storyteller’s journey. Such an approach is essential not only for business executives but also for entrepreneurs and new ventures to engage stakeholders such as customers, partners, and investors. This discussion delves into understanding the value and structure of compelling stories and storytelling related to the business, institutional, and entrepreneurial settings. It highlights the importance of the story as an opening and using other setup approaches such as SCQR (situation, complication, question, and recommendation). This article provides insights into Freytag’s three-act play structure and the role of the hero or heroine (hero(ine)) along with the Minto pyramid structure for making compelling arguments. It offers practical tips for applying storytelling techniques to help stories and storytelling resonate. Throughout this piece offers relevant examples to illustrate the why, how, and what. The discussion closes by connecting storytelling to organizational learning concepts. These include Crossan’s 4Is "feed-forward" and Roger’s diffusion of innovation theory, both of which embrace the importance of shared language and symbols that stories offer to allow for ideas, knowledge, and innovation to transcend and embed within an institution, ecosystem, or a broader universe of participants and stakeholders.